Breast milk Na+ and Na+/K+ ratio predict delayed onset of lactogenesis in gestational hyperglycemia - Rouzhi Wang; Ke Liu; Xufei Chen; Shuhan Long; Ge Yang; Dan Wang; Hongyu Li (Scientific Reports)
Abstract To investigate the predictive value of breast milk Na+ concentration and Na+/K+ ratio on delayed onset of lactogenesis (DOL) in puerpera with gestational hyperglycemia. Puerpera with gestational hyperglycemia who delivered at The First Affiliated Hospital of Army Medical University in China between October 20, 2023, and April 1, 2024, were enrolled. The concentrations of Na+ and K+ in breast milk samples were examined from study participants on days 1–3 of the postpartum period. The predictive value of Na+ concentration and the Na+/K+ ratio on DOL were assessed using receiver operating characteristic (ROC) curves. Both the Na+ concentration and Na+/K+ ratio in breast milk collected on day 3 could effectively predict DOL, with areas under the curve (AUCs) of the ROC curve and 95%CI values of 94.7% (95%CI = 0.901–0.992) and 94.2% (95%CI = 0.890–0.994), respectively. The optimized cutoffs were Na+ concentration ≥ 26.25 mmol/L (sensitivity = 88.2%, specificity = 92.2.8%) and Na+/K+ ratio ≥ 1.646 (sensitivity = 79.4%, specificity = 98.4%). Both the Na⁺ concentration and Na+/K+ ratio in breast milk were found to be effective in predicting DOL in puerpera with gestational hyperglycemia.